The Effect of Sales Distribution Channels and Promotion Policies on Consumer Buying Behavior and Its Impact on Sales Volume - Ikbal, Muh; Saragi, Sahat; Sitanggang, Maura Linda (The International Journal of Business Review (The Jobs Review), 2021)
Distribution is an important part of the sales business which influences the customer's decision to buy a product which in turn increases sales volume. The purpose of study to determine and analyze the effect of sales distribution channels and promotional policies on consumer buying behavior and its impact on sales volume. Data were analyzed using descriptive analysis and SEM (Structural Equation Modeling) SPSS 25 and AMOS 24 programs. The results showed that distribution channel has a positive and significant effect on sales volume with p-value = 0.002 with a coefficient of 0.559. Sales force has a positive and significant effect on sales volume with p-value = 0.48 and a coefficient of 0.268. Promotion policy has no effect on sales volume p-value = 0.652 (0.05) and the coefficient is 0.112. Consumer behavior has a positive and significant effect on sales volume with p-value = 0.001 with a coefficient of 0.691. Promotion policy is the weakest part in an effort to increase sales so that serious efforts are needed to fix: it is necessary to increase above the line and below the line promotional activities so that the word of mouth effect is quickly achieved;Â  making material design changes regarding citrex products to make it easier to understand and understand;Â  and conduct diverting advertisements by an increase in the promotional budget.